Resistance Breeding Increases Winter Wheat Gross Margins–An Economic Assessment for Germany - Lüttringhaus, Sophia; Zetzsche, Holger; Wittkop, Benjamin; Stahl, Andreas; Ordon, Frank; Mußhoff, Oliver (Frontiers in Agronomy, 2021)
Improved wheat varieties have ameliorated our food production. Intensive cropping systems as in Germany achieve very high grain yields and thus contribute greatly to global food security. As diseases, especially fungal pathogens, pose major threats in winter wheat production, disease management is crucial to uphold high production levels and avoid economic losses. Yet, the economic value of breeding varieties with increased resistances to fungal pathogens, has not been analyzed with comprehensive data. Our analysis fills this gap by quantifying the economic effects of 50 years of resistance breeding for winter wheat production in Germany. Based on field trials and agronomic production data, we analyze how resistances have influenced the crops’ economic profitability. Thereby we can isolate the pure breeding-induced effects of increased resistances to fungal pathogens, which cause leaf and stripe rust, powdery mildew, and Fusarium head blight. We calculated the gross margins of 176 varieties according to nitrogen and fungicide applications in field trials. Regression models show that resistance breeding had a strong positive and statistically significant effect on varieties’ gross margins. In comparison, the specific meta-environment of the season had a larger effect, whilst the effect of high nitrogen as well as fungicide treatments was lower. The gross margin increased over time along with higher resistances. Simultaneously, the difference in gross margins between the fungicide-treated and untreated variants decreased, indicating an increased contribution of resistances to yield stability. Resistances have increased gross margins greatly, as varieties’ health level stay high without fungicide applications and thus production costs can be saved. We conclude that resistance breeding has increased the economic profitability and sustainability of crop production due to a reduction of the costs for fungicides. On farmers’ fields, these positive effects of resistance breeding can be fully realized by an optimal variety choice and a variety- and situation-specific disease management. Such an agronomic practice would not only further improve winter wheat gross margins, but also mitigate some of the pressures on agricultural production such as reduced disease management options and adverse climate change impacts.